2007
DOI: 10.4103/0378-6323.35735
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoepidemiological profile of 590 cases of beetle dermatitis in western Orissa

Abstract: Beetle dermatitis should be included in the differential diagnosis of the acute onset of vesiculobullous lesions in the endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 0 publications
9
20
0
Order By: Relevance
“…1,9,12 In our study, the incidence of paederus dermatitis was highest in the summer months of April, May and June and lowest in the winter months. Similar observations were reported by Padhi et al, Gnanaraj et al and Handa et al [13][14][15] In contrast, the incidence of cases is reported to be greater during the last quarter of the year in South America and in the month of September in Iran and Guinea which could be explained by variations in habitat specificity and rainfall pattern. 1,5,9 As in previous studies, majority of affected patients in our study were students residing in hostels and villagers who lived close to moist areas, dense vegetations and agricultural farms which are the natural habitat of these insects.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…1,9,12 In our study, the incidence of paederus dermatitis was highest in the summer months of April, May and June and lowest in the winter months. Similar observations were reported by Padhi et al, Gnanaraj et al and Handa et al [13][14][15] In contrast, the incidence of cases is reported to be greater during the last quarter of the year in South America and in the month of September in Iran and Guinea which could be explained by variations in habitat specificity and rainfall pattern. 1,5,9 As in previous studies, majority of affected patients in our study were students residing in hostels and villagers who lived close to moist areas, dense vegetations and agricultural farms which are the natural habitat of these insects.…”
Section: Discussionsupporting
confidence: 41%
“…Spraying appropriate pesticides particularly in the breeding season are often helpful. 1,13,14 To conclude, Paederus dermatitis is a common condition which can be prevented by increased public awareness. We conducted a series of awareness campaigns in and around our medical campus stressing on the simple preventive measures discussed above, leading to significant reduction in the incidence of paederus dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases of periorbital dermatitis have been reported earlier from Tanzania [11] and from a study in South India [12,13]. Ocular involvement in the form of unilateral periorbital dermatitis or keratoconjunctivitis is popularly known as the "Nairobi eye".…”
Section: Discussionmentioning
confidence: 99%